KANDUNGAN NILAI MORAL DALAM NOVEL BINTANG KARYA TERE LIYE DAN KAITANNYA DENGAN PENDIDIKAN KARAKTER - Siti Fayakunikmah; Lukman Hakim (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The content of moral values in literary works, especially in star novels in which there are teachings for students at school. The purpose of this study was to describe the moral values of the novel Bintang, and the relationship between the moral values of the novel Bintang and character education in adolescents. This research uses descriptive and qualitative research methods. The data source in this research is the novel Bintang by Tere Liye. The data is in the form of sentences and words that contain moral values. Data collection techniques were carried out by reading, note-taking, and interpreting techniques. The subject of this research is the researcher himself. Data analysis used descriptive qualitative technique. The results of the research, Tere Liye's Bintang Novel with the theme of friendship in adventure teaches mutual trust and cooperation, the moral values found in Bintang's novel are related to the relationship between humans and God, humans with themselves, and humans with other humans in the social sphere.